Potencial funcional de cristas e barbelas de frango: obtenção e caracterização de peptídeos bioativos - Bezerra, Taliana Kênia A'lencar (2017)
The chicken’s comb and wattle are part of the by-products they are composed of a large number of collagenous proteins, they are considered a promising source for obtaining bioactive peptides. The objective of this thesis was to develop a technical procedure aimed at making better use of the chicken’s comb and wattle. For this, the authors carried out studies on the protein hydrolysis of a comb/wattle mixture (1:1 w/w), focusing on the production of peptides with bioactivities such as iron chelation and antioxidant capacity. At first, the following were evaluated: centesimal composition, mineral profile and protein quality (percentage of collagen, percentage of total amino acids and free amino acids, hydrophobicity profile and electrophoretic profile) of the comb, the wattle and a mixture of both (1:1 w/w). These by-products displayed a high protein concentration (61 to 83% dry base), especially proteins of collagenous origin (47 to 51% dry base). The amino acid profile presented a high level of glutamic acid (10.01 g/100g) aspartic acid (7,38 g/100g), glycine (9,05 g/100g). The minerals iron (8 mg/100g), phosphorus (337 mg/100g) and zinc (2,62 mg/100g) were present in high amounts, which emphasizes the byproducts as an excellent sources of these nutrients. Considering the protein quality of the chicken’s comb and wattle, and the absence of studies regarding their use in functional products, a study was then carried out to evaluate the obtaining of peptides from these by-products. Firstly, comparative analysis of proteolytic activity was carried out in order to select the enzyme (Alcalase, Flavourzyme, Protamex, Brauzyn and Colagenase) to be used in the hydrolysis of the comb and wattle mixture (1:1 w/w). The enzyme Alcalase displayed the highest degree of hydrolysis (DH = 19%) when compared to the other proteases (DH < 3%). After selecting the enzyme, the next step was to optimize the Alcalase hydrolysis process. The researchers selected the samples with the lowest degree of hydrolysis (< DG: enzyme substrate ratio of 1% and 60 min of hydrolysis) and the highest degree of hydrolysis (> DG: enzyme substrate ratio of 5% and 240 min of hydrolysis). These experimental samples were analyzed for their protein profile, (percentage of total amino acids and free amino acids, hydrophobicity profile and electrophoretic profile), mineral profile and were characterized according to their iron chelating and antioxidant (ABTS, DPPH e FRAP) capacities. The hydrolysate with the higher DH exhibited a higher quantity of peptides with low molecular weight and hydrophilic character, as well as a higher quantity of free amino acids. The minerals Fe, F and Zn were present in quantities that allow the samples to be characterized as sources. As for bioactivity, they showed excellent Fe2+ chelation capacity (> 94%) and antioxidant activity through the inhibition of ABTS● (> 46%), DPPH● (> 41%) and FRAP through the reduction of Fe3+ (> 95 mg/100g trolox equivalent). Comb and wattle have the potential to be used in the production of hydrolysates and are also sources of minerals and peptides with bioactivities antioxidant capacity and iron chelating. As a result of these studies, the process patent BR 10 2016 027430 3 was registered.